Young Adults’ Understanding of Modifiable Risk Factors of Infertility - Lauren Lim; Meredith Hoppe; Lauren Kennedy; Allison Gunderson; Lingchen Wang; Neda Etezadi-Amoli (Women's Health Reports)
Objective: Assess the knowledge of young adults regarding modifiable risk factors of infertility. Design: Web-based validated survey. Setting: University of Nevada, Reno (UNR). Subject(s): Undergraduate students at the UNR. Intervention(s): A survey encompassing participants’ demographics, understanding of infertility risk factors, willingness to modify behaviors to prevent infertility, personal significance of fertility, previous sources for fertility knowledge, and preferred sources for fertility education. Main Outcome Measure(s): Subject-reported knowledge of modifiable risk factors for infertility and value of fertility. Result(s): A total of 427 individuals responded. Thirty-seven percent of females indicated that oral contraceptive pills negatively impact their future fertility and 34.4% were unsure. Regarding prior use of long-acting reversible contraceptives on future fertility, 31.4% of females believed it had a negative impact and 36.9% were unsure of its impact. Only 21.7% of males thought testosterone had a negative impact on fertility. Participants were significantly more likely to avoid certain modifiable risk factors to prevent infertility than they were to avoid excessive alcohol to prevent liver disease (p = 0.008). The largest percentage of women reported obtaining the most information about their fertility from social media. Conclusion(s): Young adults would benefit from and are interested in a better understanding of their fertility and modifiable risk factors for infertility. Obstetrics and gynecology physicians and primary care providers can use these findings to guide education and address misconceptions.